UPAYA PENINGKATAN HARD SKILL SANTRI MELALUI SENI KALIGRAFI DENGAN TEKNIK GRADASI DI KABUPATEN WONOGIRI - Wahyuni, Ruslina Dwi; Yunita Sari, Vivi; Zaky Faiz, Achmad; Ratih (Inisiasi, 2024)
The research on "Mentoring in Developing Students' Interest and Creativity Through Calligraphy Art Using Gradation Techniques at TPQ Khalid Bin Walid, Mojopuro Wetan, Wuryantoro" aims to address the students' boredom in writing Arabic letters while simultaneously fostering their creativity. The method used is Participatory Action Research (PAR) with a lecture and demonstration approach. The students were provided with an understanding of calligraphy art and color gradation techniques. They then practiced coloring calligraphy using crayons and tissue with the gradation technique. The results of the study indicate that this mentoring was effective in enhancing the students' interest and creativity. The students welcomed the activity positively and showed development in creativity, while the educators also recognized significant benefits from the implementation of this mentoring. Therefore, mentoring through calligraphy art with gradation techniques has proven to be a fun and educational method in the learning process at TPQ.